„Арион эмиграции” Владислав Ходасевич в воспоминаниях Нины Берберовой Куpсив мой - Mianowska, Joanna (Acta Polono-Ruthenica, 2008)
The paper is based on memories of Wladyslaw Chodasiewicz’s wife - Nina Bierbierowa, which are good source for researching of the poetry and the personality of the poet. This source seems to be very different from the professional expressions and opinions of the critics and writers in the emigration (M. Wiszniak, W. Wejdle, G. Struve, M. Ałdanow, W. Nabokow, J. Terapiano and others) Chodasiewicz in the Bierbierowa’s memories is mainly a noble man although with many faults and doubts. In my opinion Bierbieriowa doesn’t understand fully Chodasiewicz’s poetry, his excellence and perfection, beeing concentrated mainly on understanding and knowing herself.